On Sequences of Diophantine 3-Tuples Generated through Euler Polynomials - Shanthi, J.; Gopalan, M.A.; Kumar, Sharadha (International Journal of Advanced Science and Technology, 2019)
This paper deals with the study of constructing sequences of diophantine triples such that the product of any two elements of the set added by a polynomial with integer coefficient is a perfect square 2010 Mathematics Subject Classification: 11D99